Impacts of hunting pressure on wildlife conservation in Nigeria (2018)
Hunting is a craft that is as old as mankind itself and it is one of the oldest ways for humans to use natural resources. Wildlife hunting is done in Nigeria for human consumption, medicinal purposes, ornamental use of body parts and commerce. The unsustainability of this practice has accelerated due to growing human population and thus represents a significant threat to wildlife populations. This review therefore highlights the current drivers of hunting pressure in Nigeria, assesses the impact of hunting pressure on effective wildlife conservation in Nigeria and suggests an alternative to unsustainable wildlife hunting in Nigeria. The growing human population, poverty, demand and weak penal System are recognized as the major drivers of hunting pressure on wildlife in Nigeria. The major impact of hunting pressure is the decline in the population trends of hunted wild animal species which continue to worsen over time with only a small percentage of these species considered stable or increasing. Habitat degradation, ecosystem alteration, extinction of rare species, as well as threat to sustainable ecotourism are also impacts of wildlife hunting in Nigeria. However, viable alternatives to unsustainable hunting include wildlife farming and domestication of wildlife species. This reduces the pressure and dependence on wild animal populations. Unsustainable hunting constitutes a great threat to wildlife conservation, ecotourism and environmental sustainability. In order to save wild species from further jeopardy, and for the promotion of conservation, there should be perpetual environmental protection, change in public behavior towards biodiversity, poverty eradication, establishment of more protected areas, among others.